Blade of the immortal. Omnibus X - Samura, Hiroaki; Saito, Tomoko; Simon, Philip R (Dark Horse Manga, 2019)
"Hiroaki Samura's long-running manga series ends with a massive, 704-page omnibus collection filled with action and suspense. Who will survive? Disgraced Edo officer Habaki faces the devious Anotsu in a decisive showdown, while Manji, Rin, and only a few others witness the end of an era. Rin's quest concludes with a violent bang--then things get weirder"--Back cover.